PATIENTS SAFETY CULTURE DEVELOPMENT IN JAMBI PUBLIC HOSPITAL - Anastasia Yekti Heningnurani; Dumilah Ayuningtyas (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Patient safety is a serious issue in a healthcare organization. Building a patient safety culture is the first step in the improvement of safety. As patient safety culture is an inherent component of organizational culture; therefore, a study of organizational culture is required to develop it. This study aims to analyze the patient safety culture and identify the profile of the organizational culture in the hospital to find strategies to improve the patient safety culture.Methods: This study was used the quantitative study using a cross-sectional research method, followed by a qualitative method to get descriptive information. This research conducted in Jambi Public Hospital, Indonesia with 128 respondents. Data were obtained from a survey by the HSOPSC (Hospital Survey on Patient Safety Culture) questionnaire and OCAI (Organizational Culture Assessment Instrument. Focus Group Discussion was conducted to identify obstacles and expectations in the implementation of patient safety culture. Results: The highest positive perceptions are organizational learning and continuous improvement (90.6%) and teamwork within units (78.91%). While "staffing" (39.25) and "non-punitive responses to errors" (38.54 %) are the weakest dimension of patient safety. The most dominant type of organizational culture, followed by a hierarchy with a minimal score difference. This cultural assessment serves as a guide for changes with a quality strategy of clan culture and hierarchy culture were decided in the development of patients safety culture in this hospital.Conclusion: The patient safety culture belongs to the moderate culture category, the reporting culture dimension is the weakest. A management’s commitment and staff empowerment, as well as system development, are all needed on the development of a patient safety culture. Further research is required to investigate various factors to develop the reporting culture.